Usage Features of the phraseological units in Russian political Discourse: Особенности использования фразеологизмов в российском политическом дискурсе (Journal of the College of Languages (JCL), 2021)
This article examines the usage features of the phraseological units in Russian political discourse and the peculiarities of the phraseological units’ usage by politicians in their speeches. The main focus is on the expressive and pragmatic functions of using phraseological units in political texts due to their evaluative and expressive nature. The present article also examines the structural and stylistic changes of the phraseological units in political discourse. Moreover, the work provides examples from the speeches of the Minister of Foreign Affairs of the Russian Federation S.V. Lavrov. As a result, the author comes to the conclusion that phraseological units make it possible to establish a contact between the speaker and the audience when referring to a common cultural code, to express an attitude to a certain subject. АннотацияДанная статья рассматривает функционирование фразеологизмов в российском политическом дискурсе и особенности их употребления политиками в своих выступлениях. Основное внимание сосредоточено на экспрессивной и прагматической функциях использования фразеологических единиц в политических текстах ввиду их оценочно-экспрессивного характера. Также в статье рассматриваются структурные и стилистические изменения, которые претерпевают фразеологизмы в политическом дискурсе. При этом в работе приведены примеры из выступлений министра иностранных дел РФ С.В. Лаврова. В результате автор приходит к выводу, что фразеологизмы позволяют наладить контакт адресанта сообщения с аудиторией при обращении к общему культурному коду, выразить и передать реципиентам свое отношение к предмету коммуникации.